Policy Complementarities and the Washington Consensus - Aziz, Jahangir (IMF Working Papers; Working Paper ;, 1997)
While economists continue to debate whether particular economic policies, such as those referred to in Willliamson's (1993) 'Washington Consensus,' can spur growth in developing countries, this paper demonstrates that it is combinations of policies that are more critical for growth. Policy complementarity refers to the mutually reinforcing benefits of policies that create an environment that is conducive to investment and growth. Quantitative measures of policy complementarity are developed, and the study shows empirically, through both an outcomes-based probability framework and a standard regression analysis, that these complementarities are significant and robust in explaining growth outcomes over the period 1985-95.